MICROSATELLITE DIVERSITY OF CROSSBRED HORSES RAISED IN BOSNIA AND HERZEGOVINA - Dunja Rukavina; Danica Hasanbašić; Belma Kalamujić Stroil; Naris Pojskić (Genetics & Applications, 2017)
The focus of this study was microsatellite diversity of crossbred horses raised in Bosnia and Herzegovina. Genomic DNA was extracted from blood samples of 20 individuals (KBA group – 7 individuals, crosses between Bosnian and Herzegovinian mountain horse and Arabian horse; KBR group – 9 individuals, crosses between Bosnian and Herzegovinian mountain and Belgian horses, crosses between Bosnian and Herzegovinian mountain horses and Holstein, crosses between Bosnian and Herzegovinian mountain and Lipizzaner horses and KBN group – 4 individuals, crosses between Bosnian and Herzegovinian mountain horse with an unknown origin of the other parent). The samples were profiled using 17 microsatellite markers. This method consisted of multiplex PCR procedure and generated reasonable amplification across all the loci. All samples were genotyped successfully. Considering all the observed parameters, VHL20 locus showed the highest microsatellite diversity. Locus HMS7 was the least variable in KBR group, while HMS1 locus was the least diverse in KBN group. The highest microsatellite diversity in KBA group was found at AHT5 locus while HTG6 locus was the least diverse. Obtained results suggest that the investigated populations of crossbred horses from Bosnia and Herzegovina are not affected by substantial loss of genetic diversity, as indicated by the presence of reasonably high level of genetic variation. An increase in the inbreeding coefficient and sufficient heterogenity in KBN group indicate occurrence of consanguineous mating. The present research contributes to the knowledge of current status of genetic structure of the investigated crossbred horses.